Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa - Wahyu Ningsih; Fefri Indra Arza; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This research purposed to analyse accountability of fund allocation management and gave understanding about accountability in 4 (four) villages at Sawahlunto city, West Sumatra. In order to know about how fund allocation management in that village at Sawahlunto city can be begun from strategy, action and responsibility step. This research used interpretive qualitative approach by using semi structured interview with relevant informant: village’s chairman, village’s treasurer, BPD and the society which was chosen in every village to achieve the triangulation data. The technique of collecting the data which the researcher used here was observation, semi structured interview and analytic documentation. In the strategy step, fund allocation program showed that it has done about construct society participative concept with proved in participative and responsive principle which had reached 80%, however in the transparency aspect, there is a village did not know yet about information in the strategy side. In the action step, fund allocation program in 4 (four) villages have applied participative, transparency and accountability principle. Whereas in the responsibility step, fund allocation has applied accountability principle along with implementation in the field which showed that money that was used has been accounted in a physical scale as well as administration not perfect yet. The result showed that 4 (four) villages have applied the accountability principle of fund allocation management